Counter-clockwise vortical blood flow in the main pulmonary artery in a patient with patent ductus arteriosus with pulmonary arterial hypertension: a cardiac magnetic resonance imaging case report. Issue 1 (December 2016) - Reiter, Gert; Reiter, Ursula; Kovacs, Gabor; Adelsmayr, Gabriel; Greiser, Andreas; Stalder, Aurelien; Olschewski, Horst; Fuchsjäger, Michael
Abstract Background In patients with pulmonary hypertension (PH), duration of vortical blood flow along the main pulmonary artery enables estimation of the mean pulmonary arterial pressure (mPAP) non-invasively. It remains to date not known, if this method is applicable in patients with pulmonary arterial hypertension (PAH) and abnormal aortic-to-pulmonary shunting. Case presentation The present case analyzes the effect of a patent ductus arteriosus (PDA) on pulmonary artery flow patterns in PAH (mPAP from right heart catheterization, 75 mmHg). PH-associated vortical blood flow, which is typically observed rotating in a clockwise direction when viewed in right ventricular outflow tract orientation, was found nested in PDA left-to-right shunting. Even though rotating counter-clockwise, duration of vortical flow translated into correct non-invasive mPAP estimate. Conclusions This case indicates that PH-associated vortex rotation is not restricted to clockwise direction, and that vortex-based estimation of elevated mPAP might also be feasible in patients with PAH and PDA.